The Impact of Annual Yoga Training on the Physical Fitness, Breath-Holding Time and BMI of Boarding Male Students - Kumar, Praveen; Chaudhari, Haresh G (Journal of Educational Research and Policies, 2024)
To conduct this study, ninety (N=90) male students from the Swami Brahmananda Hostel, Sri Ramakrishna Mission Vidyalaya in Coimbatore, Tamil Nadu, were chosen. Their ages ranged from 18 to 23 years. The participants underwent a year of yoga training, with sessions held daily from 6: 00 am to 7: 00 am. The physical fitness variables assessed included muscular strength, balance, hand - eye coordination, flexibility, breath - holding time, and BMI. Muscular strength was evaluated using the plank test, balance was assessed with the stork stand test, hand - eye coordination was measured with a ball toss and catch, flexibility was tested using the sit - and - reach test, and breath - holding time was measured using a nose clip. Pre - and post - training data were analyzed using the dependent t - test, with a significance level set at 0.05. The results indicated significant improvements in muscular strength, balance, hand - eye coordination, flexibility, and breath - holding time, along with a notable reduction in BMI after the year - long yoga training.